1999
DOI: 10.1073/pnas.96.14.8229
|View full text |Cite
|
Sign up to set email alerts
|

Structure of tau exon 10 splicing regulatory element RNA and destabilization by mutations of frontotemporal dementia and parkinsonism linked to chromosome 17

Abstract: Coding region and intronic mutations in the tau gene cause frontotemporal dementia and parkinsonism linked to chromosome 17. Intronic mutations and some missense mutations increase splicing in of exon 10, leading to an increased ratio of four-repeat to three-repeat tau isoforms. Secondary structure predictions have led to the proposal that intronic mutations and one missense mutation destabilize a putative RNA stem-loop structure located close to the splicedonor site of the intron after exon 10. We have determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
196
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 232 publications
(205 citation statements)
references
References 35 publications
9
196
0
Order By: Relevance
“…Three variations of the stem loop that differ in stem length have been proposed (7,9,11), but previous studies show that only the shortest predicted 18-nucleotide stem loop (Fig. 1B) is a candidate for regulating E10 splicing (17,21,24). The second hypothesis is that the ISS functions as a linear sequence that binds trans-acting factors and that FTDP-17 mutations in I10 alter this protein-RNA interaction (11,21).…”
Section: Resultsmentioning
confidence: 99%
“…Three variations of the stem loop that differ in stem length have been proposed (7,9,11), but previous studies show that only the shortest predicted 18-nucleotide stem loop (Fig. 1B) is a candidate for regulating E10 splicing (17,21,24). The second hypothesis is that the ISS functions as a linear sequence that binds trans-acting factors and that FTDP-17 mutations in I10 alter this protein-RNA interaction (11,21).…”
Section: Resultsmentioning
confidence: 99%
“…The structural features of the eukaryotic branch-site region that promote its unique recognition and chemical activity are of great interest+ Results of biochemical studies in which individual base functional groups were modified imply an extrahelical orientation of the adenine base (Query et al+, 1996), although solution NMR structures of other RNAs with unpaired adenosines show the base intercalated between adjacent base pairs (e+g+, Borer et al+, 1995;Smith & Nikonowicz, 1998;Varani et al+, 1999;see, however, Greenbaum et al+, 1996)+ Of particular interest is the RNA that forms the binding site for phage GA coat protein, because of the sequence similarity it shares with the U2 snRNA-intron branchsite pairing+ The solution structure of this RNA, characterized by an unpaired adenine that stacks within the helix (Smith & Nikonowicz, 1998), prompted us to ask whether the adenosine residue of the spliceosomal branch site is also stacked within the helix or adopts an extrahelical orientation+ Posttranscriptionally modified bases in snRNAs, including pseudouridines (c; a uridine base rotated to have a carbon-carbon glycosidic linkage and a second exposed imino group; Fig+ 1D), have long been noted+ Pseudouridines in tRNA molecules have been shown to stabilize existing helical structure by providing an additional hydrogen bond donor that participates in a water-mediated hydrogen bond with backbone phosphates (Arnez & Steitz, 1994;Davis, 1995)+ Molecular dynamics simulations support the premise that pseudouridines restrict the motion of neighboring bases (Auffinger & Westhof, 1998)+ Accordingly, the presence of pseudouridine residues has been associated with stabilization of short duplex RNAs and tRNA anticodon loops without perturbing local structure (Davis & Poulter, 1991;Hall & McLaughlin, 1991;Arnez & Steitz, 1994;Durant & Davis, 1999;Yarian et al+, 1999)+ Chemical mapping of U2 snRNA sequences of a number of species has documented many conserved pseudouridylation sites in U2 snRNA, particularly in the FIGURE 1. A: Commitment-complex snRNA-intron pairings+ The U2 snRNA pairs with the branch-site region of the intron, and the U1 snRNA forms an analogous pairing with the 59 splice site+ Sequences shown are from yeast+ c ϭ pseudouridine+ B: Yeast U2 snRNA-intron branch-site interaction shown in context with nearby U6 snRNA interactions observed upon complex B assembly (Madhani & Guthrie, 1994)+ Pairing of U2 snRNA with the branch-site sequence of the intron results in the bulging of the adenosine residue responsible for nucleophilic attack at the 59 splice site (shown by an arrow)+ Y ϭ any pyrimidine+ C: U2 snRNA-intron branch-site constructs used for NMR spectroscopy in these studies+ The unmodified duplex (uBP) and c-modified duplex (cBP) constructs are shown with open dots indicating base pairs expected from the predicted secondary structure+ So...…”
Section: Introductionmentioning
confidence: 99%
“…Most missense mutations act at the protein level and reduce the ability of tau to interact with microtubules (Hasegawa et al, 1998). Intronic mutations and the exonic mutations N279K, L284L, N296N, S305N, and S305S affect pre-mRNA processing and lead to an increase of exon 10 usage by changing either the 5Ј splice site composition or exonic elements in exon 10 (Clark et al, 1998;D'Souza et al, 1999;Hasegawa et al, 1999;Hutton et al, 1998;Spillantini et al, , 2000bStanford et al, 2000;Varani et al, 1999). As a result, the approximately equal ratio of 4R and 3R isoforms is shifted in favor of 4R tau.…”
Section: Introductionmentioning
confidence: 99%